ISTILAH ‘REMPIT’; PENGERTIAN DAN PENGGUNAANNYA DALAM ISU LUMBA MOTORSIKAL HARAM DI MALAYSIA - Rozmi Ismail; Boekhtiar Borhanuddin (Jurnal Psikologi TALENTA, 2015)
Rempit term (race) is very popular in Malaysia to use for identifying illegal motorcycle race. This research aimed to know the uses of rempit concept in the Mat Rempit group itself. The Study using 2 types of interview, the first is individual interview with 16 subjects whom had involved in rempit activity in a school at Semenyih, Selangor; the second is focus group discussion consist of 3 groups of defendant under section 42 as a result of riding motorcyle dongerously in Pulau Pinang, Johor Baharu and Kuala  Lumpur. Result of the analysis, found that rempit can be redefine as an activity of motorcycle race as together (at least consist of 2 persons) which involves race (i.e sprint or lap) and/or stunt action (i.e wheelie or wheekang) triggered by trial behavior trough engine signal from motorcycle (ramp), communication or hand gesture. A Mat Rempit (racer) is an individu who get involved in this activity. This research reviews the definition throughly by formulating rempit activity comprehensively. The implication of the research is rempit word has to be used cautiosly, especially when trying to give a label to an individual as Mat Rempit. For the future research, the definition that has to be used is the one which proposed in this research and not other vague definition.